Studies on the Aetiopathogenesis and Prevention of Brachiaria Decumbens Intoxication in Sheep in Malaysia - Zhang, Shizhen (2000)
The pathogenesis of Brachiaria decumbens intoxication has not been well explained leading to continuing outbreaks and ineffective treatment and control. Studies conducted in this thesis were aimed at elucidating the pathogenesis which in turn will lead to a better understanding of the disease and provide pragmatic strategies in treating and preventing B. decumbens intoxication. Experiments were conducted to obtain a baseline value of mineral and phytate levels in B. decumbens, the effect of feeding B. decumbens to sheep, the role of copper (Cu) in B. decumbens intoxication, the effectiveness of zinc (Zn) and its role in the prevention of B. decumbens intoxication and the isolation, characterisation and toxicity testing of the compound in B. decumbens. Samples of B. decumbens collected from five different farms representing Peninsular Malaysia were air-dried, milled and analysed for the concentration of selected minerals and phytate. In three other separate experiments, sheep were fed B. decumbens either alone, with Cu or Zn or a combination of Cu and Zn. Copper and Zn were given orally in gelatin capsules on five days of the week at a dosage of 15 mg of Cu as CUS04 5H20 and 25 mg of ZnO/kg body weight respectively. Blood and pertinent tissues were collected at fortnightly intervals and necropsy respectively. The liver function enzymes, pertinent indicators reflecting antioxidant defense and lipid peroxidation and selected minerals were monitored, and pathologic studies both at cellular and subcellular levels were also conducted. A non-critical variation of concentration of Cu, Fe and Zn and low phytate was found in all samples. Clinical signs of photosensitisation, jaundice and submandibular oedema and lesions of hepatocytic necrosis and renal damage are seen in sheep fed B. decumbens either alone or in combination with Cu and/or Zn. In all B. decumbens fed sheep, there was an impairment of the antioxidant defense and involvement of lipid peroxidation. The concentration of Cu, Fe and Zn in the grass per se is not involved in this intoxication. However, excess Cu and Zn further exacerbated the progression of the intoxication. Thus, Zn is ineffective in preventing the development of B. decumbens intoxication. Supplementation of Cu-rich by-products at any stages of B. decumbens feeding is not recommended. Studies on the isolation and characterisation of the toxic compound yielded a diosgenin. Toxicity test of diosgenin from B. decumbens in mice indicated a LD50 of 41 0.5 mg/kg. Based on the results from studies conducted, the pathogenesis of this intoxication is postulated as follows: after uptake by hepatocytes, sapogenin and its metabolites undergoes biotransformation, which is catalysed by mixed function oxidases system, yielding intermediate free radicals; hepatocytes damage at both cellular and subcellular levels due to membrane lipid peroxidation leading to interference in the transport and excretion of endogenous metabolites which in turn lead to jaundice and photosensitisation.